Hydrogeochemical press of tailing dump on the environment (By the example of Krivy Rig ore region) - KRYVORUCHKINA, O.; TERESHCHENKO, S.; BAISAROVYCH, I.; KORZHNEV, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of hydrogeochemical investigation of manmade devastative Krivy Rig's ore basin area are presented. The main objects determining hydrogeochemical regime of this region are: mine and quarry waters, tailing pits, storage ponds, Inguletch and Saksagan' rivers, cenozoic aquifers.